DEVELOPMENT OF HEALTHY PUBLIC POLICIES AND PUBLIC PARTICIPATION AFFECTING THE LIFE QUALITY OF PEOPLE IN PHETCHABUN PROVINCE - Jumponkunawut, Weerawut (Journal of MCU Nakhondhat, 2024)
The research purposes were to 1) Study the life quality of people in Phetchabun Province; 2) Analyze of healthy public policies and public participation affecting the life quality of people in Phetchabun Province; and 3) Propose the guidelines for developing the life quality of people in Phetchabun Province. This was the qualitative and quantitative research. The population was the people aged 18 years and over in the area of subdistrict municipalities; the sample group of quantitative research was the 400 people, the research instrument was the questionnaire; the sample group of qualitative research was the 20 people, the research instrument was the in-depth interview form. The data analysis statistics were the frequency, percentage, mean, standard deviation, and multiple regression analysis. The research findings were: 1) The life quality of people in Phetchabun Province found the overall was at high level, the descending mean were the environmental aspect, the social relationship aspect, the physical health aspect, and the mental aspect, respectively; 2) The development of healthy public policies and public participation found the aspects of participation in evaluation, sustainable agriculture, joint operations, community health systems, drugs and vices, and community welfare affected the life quality of people in Phetchabun Province at statistical significance level .05; and 3) Guidelines for developing the quality of life of people in Phetchabun Province found that people should be encouraged to continually undergo annual health examinations, organize training, organize activities. that can encourage people to do activities together Encourage people to have good conscience. For a sustainable quality of life for the people in the sub-district municipalities in Phetchabun Province.